Inhibitory potential test of oyster mushrooms (pleurotusspp) extract on the growth of streptococcus mutans (in vitro) - Fajriani Fajriani; Eka P. Rati (Journal of Dentomaxillofacial Science, 2019)
Objective: The objective of this study was to determine the inhibitory effect ofÂ the oyster mushroom extractÂ (pleurotusspp) on streptococcus mutans bacteria.Material and Methods: This research was a laboratory-based experimental studies with post test only control group design used Kirby Bauer agar/diffusion method. This study used extract concentrations of 20%, 30%, 50%, and positive control (chlorhekaisidin) with 4 times repetition of the treatment. The measuring instrument was a caliper with millimeters (mm).Results: One way ANOVA test showed a significant difference of the oyster mushroom extract against the inhibition zone diameter of streptococcus mutans bacteria formed at concentrations of 20%, 30%, 50%, and positive controls with a mean of 11.3 mm, 12 , 6 mm, 13.8 mm, and 19.6 mm. Data test results obtained p = 0,000 (p <0,05). This shows that oyster mushrooms extract in inhibiting the growth of streptococcus mutans bacteria were categorized as strong category.Conclusion: Oyster mushrooms extract (pleurotusspp) has inhibitory effect on streptococcus mutans bacteria.